Effectiveness and safety of olanzapine in the treatment of Asian outpatients with schizophrenia - Habil, H.; Gondoyoewono, H.; Chaudhry, H.R.; Samanwongthai, U.; Hamid, A.R.A.; Hashmi, I.T.; Budiman, R.; Knowles, A.G.; Buenaventura, R. (2007)
Objective: The objective of this study was to assess the effectiveness and safety of olanzapine in the treatment of schizophrenia among Asian patients in an outpatient setting. Methods: This was an open-label, prospective, observational study involving 339 patients from Indonesia, Pakistan, Malaysia, Thailand, and Singapore. Brief Psychiatric Rating Scale (BPRS), Clinical Global Impression Severity scale (CGI-S), and safety parameters were assessed. Results: 62 of patients responded to olanzapine treatment, defined a priori as a reduction in BPRS of > 40 from baseline. Following the 8-week treatment period, the BPRS total, BPRS positive, BPRS negative, and CGI-S scores decreased by 18.7 (95 CT: 17.4 20.2), 6.1 (5.6, 6.6), 2.9 (2.6, 3.2), and 1.5 points (median 1.0), respectively (p < 0,0001). In total, 31 of the 339 patients (9.1) failed to complete the study according to the study description. Loss to follow-up and personal conflict were the most common reasons for discontinuation. There were 30 treatment-emergent adverse events with six serious cases, assessed as unrelated to study drug, reported. Conclusion: This study further demonstrates the effectiveness and safety of olanzapine in actual clinical practice settings, in reducing the severity of psychopathological symptoms in Asian patients with schizophrenia.